New Swift UVOT transient SWIFT J004255.6+411412 in M 31 - Hofmann, F.; Sturm, R.; Greiner, J.; Vasilopoulos, G.; Maggi, P. (The Astronomer's Telegram, 2013)
In a monitoring observation of the central region of the Andromeda Galaxy (M 31) with the Ultra-violet/Optical Telescope (UVOT) on board the Swift satellite (ObsID 00035336102, starting 2013-05-27.15 UT), we detected a new UV transient (UVW1 filter, 181-321 nm). The source is located at RA 00h 42m 55.62s, Dec +41d 14' 12.3" (± 0.5", J2000, 90% confidence level). The following table lists the Swift ObsID, the MJD at the beginning of the exposure, UVW1 magnitudes (Vega system), and 1σ statistical uncertainties.
Keywords: Nova; Star; Transient; Ultra-Violet